1989
DOI: 10.1111/j.1600-079x.1989.tb00417.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Differences in Glucose Tolerance and Insulin Response of Pinealectomized Pigeons (Columba livia)

Abstract: The effects of a glucose tolerance test (GTT) and an insulin response test (IRT) on blood glucose levels were evaluated in pinealectomized and nonpinealectomized pigeons during the breeding and nonbreeding months. The tests revealed increased glucose tolerance and insulin sensitivity in pinealectomized birds during the breeding season. In the nonbreeding season, both the pinealectomized and the control birds tended to show more or less similar responses for both GTT and IRT. These changes confirm the anti-insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The per minute rate of glucose elevation (E), adrenaline-induced glucose elevation (Ea), glucagon-induced glucose elevation (Eg) and per minute clearance rate (A) under GTT, the insulin-induced clearance rate (Ki), adrenaline-induced clearance rate (Ka), glucagon-induced clearance rate (Kg),and the post-insulin-induced glucose normalisation rate (JVz) were calculated by the method described by Patel and Ramachandran (1989) and Ramachandran and Patel (1989) (Table 1). Table 1 also indicates the E/K, Ki/Ni, Eg/Kg and Ea/Ka ratios.…”
Section: Resultsmentioning
confidence: 99%
“…The per minute rate of glucose elevation (E), adrenaline-induced glucose elevation (Ea), glucagon-induced glucose elevation (Eg) and per minute clearance rate (A) under GTT, the insulin-induced clearance rate (Ki), adrenaline-induced clearance rate (Ka), glucagon-induced clearance rate (Kg),and the post-insulin-induced glucose normalisation rate (JVz) were calculated by the method described by Patel and Ramachandran (1989) and Ramachandran and Patel (1989) (Table 1). Table 1 also indicates the E/K, Ki/Ni, Eg/Kg and Ea/Ka ratios.…”
Section: Resultsmentioning
confidence: 99%
“…Although an early study indicated that insulin could enhance pyruvate utilization and promote pigeon muscle growth ( Stadie et al, 1948 ), research has also reported that insulin injection did not increase prolactin levels in pigeon crop mucosal epithelium ( Anderson et al, 1987 ). Additionally, Ramachandran and Patel (1989) reported that insulin was increased during the breeding stage and decreased during the nonbreeding stage to regulate glucose levels to improve pigeon crop milk synthesis and promote squab growth. Interestingly, a recent study found that insulin receptor mRNA abundance in male pigeon crop tissue changed slightly during incubation or after hatching, while in females, it peaked at d 4 after hatching and then decreased sharply ( Xie et al, 2018 ).…”
Section: Hormonal Changes and Signaling Pathways Involved In Pigeon C...mentioning
confidence: 99%